E-Booklet Based Learning Media to Increase Motivation and Learning Outcomes - Nurjanah, Fitri; Astuti, Rina (Universitas Muhammadiyah Surakarta, 2024)
Learning is an activity that involves educators and students. In implementing learning, teaching staff still carry out learning using conventional methods. Appropriate learning media will increase student motivation and learning outcomes. Instructional Media e-booklet is a media used to convey learning material in the form of summaries and attractive images on an electronic basis. The purpose of this research is to find out use of media-based learning e-booklet to foster motivation and learning outcomes for SMA Negeri 5 Metro City students. Research result in the experimental class the average value pretest namely 53.61 and the average value posttest namely 77.5. Meanwhile in the control class the average value pretest namely 60.83 and the average value posttest 66,11. Media based learning e-booklet can improve student learning outcomes based on the results of analysis.